Control of fraud and unauthorized payments in the MFS industry: An exploratory study of bKash Limited - Benazir, Nafisa Sadaf (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.